Psychosocial Development Refers to the Lifelong Process Through (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The study explored The Influence of Qur’anic Engagement on Psychosocial Development among Adolescents in Jos, Nigeria. This qualitative study explored how Qur’anic engagement (recitation, memorization, and study) influences psychosocial development (identity formation, resilience, and social connectedness) among Muslim adolescents in Jos, Nigeria. Using purposive and snowball sampling, 42 participants (aged 12–19) actively engaged in Qur’anic activities were recruited for semi-structured interviews and focus group discussions. Thematic analysis revealed four key mechanisms linking Quranic engagement to psychosocial well-being: moral guidance (52% of participants), stress reduction (38%), community belonging (28%), and divine reliance (tawakkul) (22%). Findings demonstrated a dose-dependent relationship, with daily engagers reporting the strongest benefits, particularly those fluent in Arabic, who exhibited deeper cognitive-emotional growth compared to non-Arabic speakers who derived more ritual-based comfort. Gender differences emerged, with males emphasizing identity prestige and females prioritizing emotional coping. Based on these findings, recommendations include integrating Tafsir (exegesis)-based Quranic education into school curricula, expanding psychosocial-supportive halaqas (study circles), and developing faith-integrated mental health interventions for Muslim adolescents.